Analysis Of The Influence Of Csr On Financial Inclusion, Financial Performance, Financial Stability And Company Value In The Banking Sector In Indonesia - I Made Pradna Wirakanada (Institut Manajemen Wiyata Indonesia & Asosiasi Peneliti Manajemen Indonesia, 2023)
The influence of globalization, increasingly fierce competition and the availability of adequate access to information forces companies to rethink appropriate business strategies to compete. Of the many existing strategies, companies need to consider CSR as one of the business strategies. This research analyzes the impact of implementing CSR as independent variable on financial inclusion, financial performance, financial stability and company value as dependent variables in the banking sector in Indonesia. We use the data of 20 companies from 2018 to 2022. Method used in this research is linier data regression. The result shows that CSR only have a significant influence on financial inclusion and firm value while for control variables, only tangibility that has no impact on all four factors.